Social Status and Opioid Drugged Driving - Rookey, Bryan D (Journal of drug issues, 2023)
This study examines the effects of social status on opioid drugged driving fatalities in the context of the ongoing opioid mortality crisis. Broad criminological insights are leveraged to understand how position in the age, race, and sex status hierarchies impacts opioid use by drivers. Analysis of data from the Fatality Analysis Reporting System shows that fatally injured drivers who used opioids prior to the crash were more often male, White, non-Hispanic, and older compared to other statuses. Moreover, the social statuses of opioid drugged drivers are dissimilar to those who used opioids in drug overdose deaths. Results suggest that social status-informed and driver-focused initiatives may be particularly effective in reducing opioid use by drivers.